2022
DOI: 10.1089/nat.2021.0043
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Safety and Efficacy Data of Golodirsen in Ambulatory Patients with Duchenne Muscular Dystrophy Amenable to Exon 53 Skipping: A First-in-human, Multicenter, Two-Part, Open-Label, Phase 1/2 Trial

Abstract: The aim of this Phase 1/2, 2-part, multicenter trial was to report clinical safety and efficacy of long-term golodirsen treatment among ambulatory patients with exon 53 skip-amenable Duchenne muscular dystrophy (DMD). Part 1 was a 12-week, randomized, double-blind, placebo-controlled, dose-titration study followed by 9-week safety review. Part 2 was a 168-week, open-label evaluation of golodirsen 30 mg/kg. Part 1 primary endpoint was safety. Part 2 primary endpoints were dystrophin protein expression and 6-min… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
43
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(46 citation statements)
references
References 43 publications
2
43
0
1
Order By: Relevance
“…DMD is a rare disease, and only 8%-10% of DMD patients have a variant amenable to exon 53 skipping [3]. While the small sample size (N = 16) represents a limitation of this study, both the study design and sample size are consistent with other studies investigating potential approaches to treatment for this patient population [21][22][23][24]. An additional limitation is the use of an historical control group (group-level matched) in this study, rather than a placebo arm.…”
Section: Limitationssupporting
confidence: 57%
See 1 more Smart Citation
“…DMD is a rare disease, and only 8%-10% of DMD patients have a variant amenable to exon 53 skipping [3]. While the small sample size (N = 16) represents a limitation of this study, both the study design and sample size are consistent with other studies investigating potential approaches to treatment for this patient population [21][22][23][24]. An additional limitation is the use of an historical control group (group-level matched) in this study, rather than a placebo arm.…”
Section: Limitationssupporting
confidence: 57%
“…Long-term data on the use of FDA-approved DMD therapies are beginning to emerge. A recent paper by Servais and colleagues found that golodirsen treatment in DMD patients (n = 25, mean age 8.4 years) amenable to exon 53 skipping did not significantly reduce loss of ambulation, 6MWT, or forced vital capacity evaluations at 3 years relative to external controls [21]. Viltolarsen (presented here) and golodirsen target the same DMD gene exon 53.…”
Section: Discussionmentioning
confidence: 58%
“…The long-term clinical efficacy of these therapies has been confirmed in recent reports (Nelson et al 2019;Servais et al 2022;Xu et al 2019), however the risks associated with off-target mutations and tumorigenicity still raise significant safety concerns.…”
Section: Introductionmentioning
confidence: 98%
“…Golodirsen was first tested in a 24-week placebo-controlled, dose-escalation study of 12 participants [ 36 ]. Thirty-nine participants were then enrolled in a long-term extension study (NCT02310906).…”
Section: Exon Skippingmentioning
confidence: 99%